Odpowiedzialność za środowisko w orzecznictwie indyjskim: brak - Florek, Iwona (Studia Prawnoustrojowe, 2019)
Environmental protection policy is the domain of every country with services ratifed in international agreements. India sets its own development direction in this respect. The judiciary also plays an important role in the system of common law as a tool for defning the legal framework. India applies environmental principles which follow international environmental protection. The purpose of this paper is to present legal provisions in the feld of environmental protection in the Republic of India and the state and direction of case law with particular emphasis on the role of man, his health, quality of life and the right to live in a clean environment.